Pendampingan Pembuatan Digital Worksheet Menggunakan Wizer.Me Berkonteks Seni Budaya Ogan Komering Illir - Susanti, Ely; Simarmata, Ruth Helen; Sukmaningtias, Novika (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
In implementing differentiated learning, teacher competence is needed in developing learning tools that are integrated with technology. Digital worksheets are needed to apply concepts and achieve the expected abilities to achieve learning indicators in the curriculum. Transforming culture in learning is an important part of education. This service activity is structured with a process of assisting Pagar Alam City Mathematics MGMP teachers in designing digital worksheets for differentiated learning in the context of Ogan Komering Illir arts and culture. Assistance activities for creating digital worksheets are carried out synchronously and asynchronously with the aim of increasing teachers' pedagogical competence in developing digital worksheets, guiding teachers in producing and implementing digital worksheets. In order to support the implementation of differentiated learning that has good quality as part of the independent curriculum, the service team, assisted by undergraduate, postgraduate and alumni students, provides assistance to Pagar Alam City MGMP teachers in creating the digital worksheet. Service activities show that participants respond positively to this activity. === Dalam mengimplementasikan pembelajaran berdiferensiasi, kompetensi guru sangat dibutuhkan dalam mengembangkan perangkat pembelajaran yang terintegrasi dengan teknologi. Digital worksheet dibutuhkan dalam menerapkan konsep dan mencapai kemampuan yang diharapkan untuk mencapai indikator pembelajaran pada kurikulum. Tranformasi budaya dalam pembelajaran, khususnya pembelajaran matematika, merupakan bagian penting dalam pendidikan. Kegiatan pengabdian ini disusun dengan proses pendampingan pada guru-guru MGMP Matematika Kota Pagar Alam dalam merancang digital worksheet untuk pembelajaran berdiferensiasi dengan konteks seni budaya Ogan Komering Illir. Kegiatan pendampingan pembuatan digital worksheet dilakukan secara synchronous dan asynchronous dengan tujuan untuk meningkatkan kompetensi pedagogik guru dalam mengembangkan digital worksheet serta membimbing guru-guru dalam menghasilkan dan mengimplementasikan digital worksheet. Demi mendukung terlaksananya pembelajaran berdiferensiasi yang berkualitas, tim pengabdian dengan dibantu oleh mahasiswa sarjana, pascasarjana, dan alumni melaksanakan pendampingan terhadap guru-guru MGMP Kota Pagar Alam dalam pembuatan digital worksheet tersebut. Kegiatan pengabdian menunjukkan peserta merespons kegiatan ini dengan positif.